Assessing the cost competitiveness of China's shipbuilding industry - Liping Jiang; Siri Pettersen Strandenes (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2011)
Cost has a significant impact on competitiveness within the shipbuilding industry. In China, low costs have created favourable conditions for domestic shipyards competing in the international market. However, China's shipbuilders have been facing rising cost pressures in recent years, which may affect their industrial competitiveness. In this article, we assess China's shipbuilding cost and its impact on the competitiveness of China's shipbuilding industry. We make comparisons with China's major competitors, South Korea and Japan, over the period from 2000 to 2009. First, we analyse principal factors that affect shipbuilding cost. Second, we examine the changes in China's shipbuilding cost over the time period. Finally, we use shipbuilding cost and market share as the basis for analysing the competitiveness of the shipbuilding industry. The results reveal the sources and limiting factors of China's cost advantage, as well as changes in its shipbuilding cost and competitiveness.
Keywords: 330; shipbuilding cost; industry competitiveness; China's shipbuilding industry; Schiffbau; Komparativer Vorteil; Marktanteil; Vergleich; China; Japan; Südkorea